2021
DOI: 10.1016/j.tim.2021.03.016
|View full text |Cite|
|
Sign up to set email alerts
|

Durability of Immunity to SARS-CoV-2 and Other Respiratory Viruses

Abstract: Even in nonpandemic times, respiratory viruses account for a vast global burden of disease. They remain a major cause of illness and death and they pose a perpetual threat of breaking out into epidemics and pandemics. Many of these respiratory viruses infect repeatedly and appear to induce only narrow transient immunity, but the situation varies from one virus to another. In the absence of effective specific treatments, understanding the role of immunity in protection, disease, and resolution is of paramount i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 131 publications
0
35
0
4
Order By: Relevance
“…34 Among other respiratory viruses, including the seasonal coronaviruses, respiratory syncytial virus, and influenza virus, infection tends to lead to the production of neutralising antibodies that are transiently protective against reinfection. 35 Natural infection studies have shown that waning protective immunity allows for reinfection with seasonal coronaviruses within a 12-month window (although strain variation, not accounted for in these studies, might partly explain this short-lived immunity). 36,37 In a study of adults naturally infected with respiratory syncytial virus, 73% (11 of 15) were reinfected within an 8-month period, 38 whereas in an infant study, 36% (45 of 125) were reinfected in a 24-month period from birth, with the risk of reinfection negatively correlating with the neutralising antibody titre from the previous infection.…”
Section: Sars-cov-2 Immunity In Contextmentioning
confidence: 86%
“…34 Among other respiratory viruses, including the seasonal coronaviruses, respiratory syncytial virus, and influenza virus, infection tends to lead to the production of neutralising antibodies that are transiently protective against reinfection. 35 Natural infection studies have shown that waning protective immunity allows for reinfection with seasonal coronaviruses within a 12-month window (although strain variation, not accounted for in these studies, might partly explain this short-lived immunity). 36,37 In a study of adults naturally infected with respiratory syncytial virus, 73% (11 of 15) were reinfected within an 8-month period, 38 whereas in an infant study, 36% (45 of 125) were reinfected in a 24-month period from birth, with the risk of reinfection negatively correlating with the neutralising antibody titre from the previous infection.…”
Section: Sars-cov-2 Immunity In Contextmentioning
confidence: 86%
“…Therefore, the results for adults should not be overinterpreted as only a small sample of 0.5% of the total adult population in the city was investigated. SARS-CoV-2 antibodies indicate that a person has been infected (and/or COVID-19 vaccinated) and IgGs can be detected in the blood as soon as two weeks after infection (23) and beyond. This is consistent with previous findings (24), where about two-thirds of the mild COVID-19 adult controls still had RBD binding IgG titres 6 months after symptom onset in blood -but also in saliva although at a lower magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…An initial waning of antibody titres is typically seen after resolution of an acute viral infection. 3,4 In the case of some viruses, long-lived plasma cells are then able to maintain antibodies for decades. [5][6][7] By contrast, in the months following infection with other viruses, including human coronaviruses like SARS-CoV-2, neutralising antibodies continue to wane and can drop below the threshold of detection in a proportion of individuals.…”
Section: Introductionmentioning
confidence: 99%